Hubungan Skor Perototan Ayam Betina Pembibit dan Performa Produksi - Agus Kadarisman; Rudi Afnan; Sumiati Sumiati (Jurnal Ilmu Pertanian Indonesia, 2024)
One think In the Parent Stock breeder farm is Scoring Fleshing in growing periode The purpose of this study was to examine the effect of the fleshing score on the production performance of parent stock hens and find problems in the form of deviations from the fleshing score along with evaluations, solutions, and improvement plans. The benefit of this research is to provide information and guidance for farm supervisors and managers regarding target fleshing. Measuring the fleshing score is done by directly measuring the thickness of the chicken breast muscles. The number of samples taken is 5% of the total population ( COBB 2022 ). The data processed by excel 2021 and descriptive analised in order to same with the filed. Fleshing score aims to maintain and monitor body weight so that it is maintained, not to be overweight or otherwise the chickens become too thin. Good fleshing will produce enough fat reserves. This fat reserve is useful for preparation before production. The next hope is that with sufficient fat reserves during production, peak production will be high and production performance will be more persistent. Hens in coops that achieve an ideal fleshing score (less fleshing score 2) in the growing period tend to show better performance during the laying period, lower depletion of laying, higher peak production, higher cumulative PE, and higher cumulative HE. Keywords: flashing score, parent stock, production performance